PHYSICOCHEMICAL, MINERALS AND ANTIOXIDANT PROPERTIES OF Labisia pumila var. alata OF SELECTED GEOGRAPHIC ORIGIN - Iwansyah, Ade Chandra; Yusoff, Mashitah Mohd (AGRIVITA, Journal of Agricultural Science, 2012)
In this study, relationship between physicochemical, mineral and antioxidant properties of water-soluble extracts of Labisia pumila var. alata is proposed. A wide range of analytical parameters were studied including physicochemical viz., proximate composition, yield, pH, total solid, total acidity, solubility; minerals content (Ca, Fe, and Zn) and heavy metals (Cd, Hg, As, and Pb); total phenolic content (TPC), tannins content, gallic acid (GA) content, and free scavenging activity of DPPH (EC50). Data were analyzed by ANOVA and principal component analysis (PCA). Based on the PCA analysis, TPC, GA content, moisture content, crude protein, and zinc content havesignificantly positively correlated (r close to 1) to antioxidant activity. Cluster analysis (CA) resulted in four groups of LP.These results provide useful data about the studied relationships and chemical patterns in LP leaves.